Strategic Use of Accounting Information and Its Impact on MSMEs’ Understanding of SAK EMKM Based on Firm Size - Mishelei Loen; Herry Winarto; Daniel Erinopem Situmorang (SAN Scientific, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy. However, many MSMEs have difficulty implementing accounting standards due to limited accounting knowledge and limited information. This study aims to analyze the effect of information provision and socialization, accounting understanding, and business size on MSMEs' understanding of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Using a quantitative approach, data were collected from 36 MSMEs in Bekasi. The results show that information provision, socialization, and accounting understanding have a positive and significant effect on MSMEs' understanding of SAK EMKM. However, business size does not have a significant effect. This finding emphasizes the importance of accounting socialization and training to improve the quality of MSME financial reports. To improve MSMEs' understanding of SAK EMKM, management should prioritize implementing structured accounting training and socialization. This program can involve a practice-based approach, such as simple financial recording simulations, direct training, and technical assistance. In addition, strategic policies are needed that support the accessibility of information through digital media to reach more MSME actors.